Climate Change in a Chromium World: Estrangement and Denial in Ted Chiang’s “Exhalation” - Essi Vatilo (Fafnir, 2019)
This article discusses Ted Chiang’s “Exhalation” as a story of climate change with the potential to resist polarisation of attitude and different forms of denial. Through the lenses of naturalisation and world reduction the story can be seen to recontextualise climate change. As the mechanical inhabitants of the chromium world of the story contemplate their role as agents of their own demise, the story addresses the material and psychological impact of climate change. The process of naturalisation and the resultant estrangement disentangle climate change from real-world politics and polarised attitudes, while at the same time drawing attention to them. World reduction simplifies the science and politics of climate change, and thereby undermines the reasoning behind different levels of denial.